Biological applications of diamond electrodes; electrochemical studies of riboflavin - Chatterjee, A; Foord, J (2009)
The electrochemical study of flavines is a challenge using many solid-state electrode materials, since pronounced adsorption effects are observed which have deleterious effects on the recorded observations. In the present work three distinctive types of diamond electrode are employed to measure electrochemical charge transfer to riboflavin. At nanodiamond, it is found that rapid charge-transfer kinetics are observed, between the electrode and an adsorbed layer of around 2 monolayers thickness which rapidly forms at the electrode surface. In contrast, high phase purity microcrystalline diamond electrodes, show little adsorption, enabling solution phase diffusion controlled electrochemistry to be observed. Studies of the pH dependence of the observed electrochemistry are presented, which show results comparable to those observed at dropping mercury electrodes, and electrochemical measurements in the presence of power ultrasound are also described. © 2009 Elsevier B.V. All rights reserved.